Effect of three diets on the growth and fatty acid profile of the common ragworm Hediste diversicolor (O.F. Müller, 1776) - Santos, António (2019)
The polychaete Hediste diversicolor has a high physiological tolerance to extreme environmental factors, being easily farmed and reproduced in different types of conditions. Both in the field and under laboratory conditions, this worm can feed on different types of food. In order to highlight the potential of H. diversicolor for aquaculture, specific growth rate (SGR), daily growth rate (DGR), survival rate and fatty acid profile of juvenile worms, fed with three different diets, were assessed. The experiments were conducted using juvenile polychaete from a controlled reproduction with wild adults. H. diversicolor individuals were fed with two commercial diets, seabream dry feed (Aquagold) and semi-wet pellets for reared sole (Moist Sole), and with a non-processed diet consisting on mackerel's fillets (Trachurus trachurus). Juveniles fed with Aquagold had the highest final individual weight (0.89 ± 0.10 g). The SGR was higher in H. diversicolor fed with Aquagold and Moist Sole, (6.49 ± 0.30% d−1 and 6.54 ± 0.06% d−1, respectively. The highest DGR was observed for juveniles fed with Aquagold (0.146 ± 0.02 g d−1). The survival rate of ragworms under different treatments ranged from 96 to 100%. Regarding the protein content, the Moist Sole diet provided the highest percentage of protein in the reared worms (8.87%). Results showed that the total fat content of the diets was reflected in the fat content of the reared worms. The Moist Sole diet treatment had the highest fat content (2.25%) and individuals fed with seabream dry feed showed similar results (2.18%), while the lowest percentage was observed for the mackerel diet (0.85%). According to the fatty acid profile, the major fatty acids found in the juveniles fed with the three different diets were palmitic (C 16:0), with a higher value in the individuals fed with mackerel's fillets. Oleic (C 18:1 n9), eicosapentaenoic (C 20:5 n3), docosahexaenoic (C 22:6 n3) and stearic (C 18:0) acids presented high values in H. diversicolor fed with all the experimental diets. Statement of Relevance: The common ragworm Hediste diversicolor is a potential high quality fatty acids source for reared fish and shrimp. Previous studies suggested that diet could be a relevant factor affecting the fatty acid composition of this polychaete (Luis and Passos, 1995). This study aimed to assess the effect of different diets on growth and survival of common ragworms juveniles (H. diversicolor), as well as the fatty acid profile and protein content in their tissues, aiming to find an appropriate diet to be used in commercial aquaculture.